Hardcore Visual Basic - McKinney, Bruce, 1953-. (Microsoft programming series., 1995)
The spirit of Basic; The second level of Basic enlightenment; Basic tolls the Old-Fashioned way; An object way of Basic; Taking control of Windows; Painting pictures; A handle on data; Don't write the same code twice; Stir-fry; The Ole gospel; The new frontier.